Perception of Female Media Workers on Wearing Hijab/Abaya at Workplace in Pakistan (Al-Qamar, 2022)
Hijab or abaya, a symbolic dress code that the Muslim women wear across the globe and reflect it as their identity has been subject to great sociocultural and scholarly debate across the globe. Many studies have been conducted in the West about the discrimination faced by the Muslim women due to wearing hijab or abaya, as a result of Islamophobia that prevails in those societies. Following the trend, many studies have also been conducted in the Muslim countries including Pakistan about wearing hijab or abaya at workplace that predominantly reflect inclination towards discrimination faced by the working women. Adding to the global academic debate on the topic, the current study attempts to explore the perception of female media workers about wearing hijab or abaya at workplace in Pakistan through in-depth interviews. A conclusive understanding of the research states that contrary to many research studies across the globe as well as in Pakistan, environment in Pakistani media organizations regarding wearing hijab or abaya at workplace is quite conducive, but usually off-screen.
Keywords: Hijab; Abaya; Female Media Workers; Pakistan